2019
DOI: 10.1073/pnas.1905527116
|View full text |Cite
|
Sign up to set email alerts
|

A safe and sustainable bacterial cellulose nanofiber separator for lithium rechargeable batteries

Abstract: Bacterial cellulose nanofiber (BCNF) with high thermal stability produced by an ecofriendly process has emerged as a promising solution to realize safe and sustainable materials in the large-scale battery. However, an understanding of the actual thermal behavior of the BCNF in the full-cell battery has been lacking, and the yield is still limited for commercialization. Here, we report the entire process of BCNF production and battery manufacture. We systematically constructed a strain with the highest yield (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 31 publications
(38 reference statements)
1
48
0
Order By: Relevance
“…Heterologous overexpression of two of these targets, glucose-6-phosphate isomerase (pgi) and phosphogluconate dehydrogenase (gnd) brought enhanced BNC production, which was 2-fold for the strain overexpressing the E. coli pgi gene. In another study of this team, exploiting this GEM and through simulated FBA, it was found that the inclusion of a reaction catalysed by phosphofructokinase (pfkA), which is absent in the Komagataeibacter spp., improves cellulose production rate and specific growth rate (discussed later; Gwon et al 2019).…”
Section: Genome-scale Metabolism Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…Heterologous overexpression of two of these targets, glucose-6-phosphate isomerase (pgi) and phosphogluconate dehydrogenase (gnd) brought enhanced BNC production, which was 2-fold for the strain overexpressing the E. coli pgi gene. In another study of this team, exploiting this GEM and through simulated FBA, it was found that the inclusion of a reaction catalysed by phosphofructokinase (pfkA), which is absent in the Komagataeibacter spp., improves cellulose production rate and specific growth rate (discussed later; Gwon et al 2019).…”
Section: Genome-scale Metabolism Modellingmentioning
confidence: 99%
“…In both studies, the observed increase of cellulose production yield by the VHb+ strains was in the range of 1.5-to 1.7-fold. A more recent study involving K. xylinus DSM 2325 strain has shown that the reduction of gluconic acid production can be achieved through manipulation of regulatory proteins, besides the direct catabolic enzymes (Gwon et al 2019). This study generated a strain with reduced gluconic acid synthesis yield (39.2% in the mutant and 64.8% of glucose in the parental strain) after introduction of an additional copy of the crp (Crp/Fnr) gene, expressed from a plasmid, under the tac promoter control.…”
Section: Improvement In Cellulose Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…BC has outstanding properties, such as high water retention value, surface area, crystallinity, biodegradability, biocompatibility, and high purity due to the absence of lignin and hemicellulose [3][4][5][6]. Due to these properties, BC has potential applications in the biomedical, cosmetic, automotive, packaging, health food, electrical, and sensor industries, with a rapidly increasing commercial value [7][8][9].…”
Section: Introductionmentioning
confidence: 99%